Aggregatibacter actinomycetemcomitans-Gram-Negative Bacterial Pathogen - Johansson, Anders; DiRienzo, Joseph M. (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
Aggregatibacter actinomycetemcomitans is a well-studied Gram-negative bacterium that can often be found in the oral cavity of young individuals. It has several virulence factors and a large genetic diversity, which results in both harmless and highly virulent genotypes. To determine the virulence potential of the isolated bacteria, genetic profiling is recommended. Advanced knowledge of the virulence mechanisms induced by this bacterium is important for the development of future personalized preventive and treatment strategies. The fifteen papers in this book provide a strong and relevant background that can contribute to the improvement of future diagnosis and research strategies.